PENGARUH FAKTOR BUDAYA, SOSIAL, PRIBADI, PSIKOLOGI, DAN BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN KEBAYA PADA BUTIK LESTARI DI DENPASAR - Putri Anggreni; Putu Wahyu Pratiwi (Forum Manajemen, 2020)
The purpose of this study was to obtain explanative findings that tested the influence of social factors on purchasing decisions, cultural factors on purchasing decisions, personal factors on purchasing decisions, psychological factors on purchasing decisions, and the marketing mix of purchasing decisions. The research design used in this research is a causal quantitative research design. Methods of data collection using questionnaires, which then analyzed by using multiple regression with the classical assumption test. The result of research indicate that there is significant influence froom social factor to purchasing decision with contribution of 76.9%, cultural factor to purchasing decision with contribution of influence equal to 93.8% and personal factor to purchasing decision with contribution of 61.4%, psychological factor to purchase decision of influence contribution equal to 51.4%, and marketing mix to purchasing of influence contribution equal to 52.9%.